Contribuição ao estudo anatômico dos ramos sacrais da aorta abdominal do gato (Felis catus) - Geraldo, Bruna [UNESP]; Silva, José Ricardo de Carvalho Pinto e [UNESP]; Schimming, Bruno Cesar [UNESP]; Guazzelli Filho, Joffre [UNESP]; Filadelpho, André Luiz (My University, 2013)
The objective of this study was to describe the cat abdominal aorta anatomy, emphasizing the common iliac, external iliac, internal iliac and median sacral arteries. It was used 10 animals from Unesp/Botucatu . The animals injected with formol were dissecated and examined. The abdominal aorta emits rami constituting external and internal iliac arteries. In 100% of cases, the median sacral artery presents caudally like the abdominal aorta continuation always with small caliber.

O objetivo deste estudo foi descrever a anatomia da aorta abdominal do gato enfatizando as artérias ilíacas comuns, artérias ilíacas externas e internas e a artéria sacral mediana. Utilizamos 10 animais da Unesp/Botucatu. Os animais injetados com formol foram dissecados e examinados. A aorta abdominal emite ramos constituindo as artérias ilíacas externas e internas. Com relação à artéria sacral mediana em 100% dos casos se apresenta caudal como continuação da aorta abdominal e sempre com calibre menor.
Contribution to the study of anatomical ramos sacral abdominal aortic cat (Felis catus)
Keywords: Anatomy; Cat; Aorta; Anatomia; Gato; Aorta